(3x-4x+2y)*(2y+3y+2x)=

Simple and best practice solution for (3x-4x+2y)*(2y+3y+2x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-4x+2y)*(2y+3y+2x)= equation:


Simplifying
(3x + -4x + 2y)(2y + 3y + 2x) = 0

Combine like terms: 3x + -4x = -1x
(-1x + 2y)(2y + 3y + 2x) = 0

Reorder the terms:
(-1x + 2y)(2x + 2y + 3y) = 0

Combine like terms: 2y + 3y = 5y
(-1x + 2y)(2x + 5y) = 0

Multiply (-1x + 2y) * (2x + 5y)
(-1x * (2x + 5y) + 2y * (2x + 5y)) = 0
((2x * -1x + 5y * -1x) + 2y * (2x + 5y)) = 0

Reorder the terms:
((-5xy + -2x2) + 2y * (2x + 5y)) = 0
((-5xy + -2x2) + 2y * (2x + 5y)) = 0
(-5xy + -2x2 + (2x * 2y + 5y * 2y)) = 0
(-5xy + -2x2 + (4xy + 10y2)) = 0

Reorder the terms:
(-5xy + 4xy + -2x2 + 10y2) = 0

Combine like terms: -5xy + 4xy = -1xy
(-1xy + -2x2 + 10y2) = 0

Solving
-1xy + -2x2 + 10y2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-2x + -5y)(x + -2y) = 0

Subproblem 1

Set the factor '(-2x + -5y)' equal to zero and attempt to solve: Simplifying -2x + -5y = 0 Solving -2x + -5y = 0 Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. -2x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 -2x + 0 = 0 + 5y -2x = 0 + 5y Remove the zero: -2x = 5y Divide each side by '-2'. x = -2.5y Simplifying x = -2.5y

Subproblem 2

Set the factor '(x + -2y)' equal to zero and attempt to solve: Simplifying x + -2y = 0 Solving x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 x + 0 = 0 + 2y x = 0 + 2y Remove the zero: x = 2y Simplifying x = 2y

Solution

x = {-2.5y, 2y}

See similar equations:

| -2x-5(x+1)=-x | | 6e^3x=30 | | 11[5-(4-2x)]+10x=4(8x+4)-5 | | w(26)=3x-1 | | xFactor+3x+2=0 | | y=.5x+-19 | | 5x-36=34+4x | | 5x+4(x-2)=10x+6 | | -2x+5x-14=3(x-1)-26 | | 1.2(b-12)=84 | | g=8y-m/y | | -x-2=-3x-5 | | 0.6x+14.8=x-1.56 | | 331.11=9(0.08m+26.90+0.10(26.90)) | | x^3-1/4x^2-2x-3=0 | | 6x+6.4=2(4x-2.8) | | 245=70+t | | 3(2x+7)=5x+17+x | | 2q+457=875 | | [(x-10)-24]+(x-10)+x=180 | | 8x+3-10=-2(x-2)+3 | | -3(t-2)+8t=7t-4 | | 4t+13b=487 | | 0.2x+0.5=-0.1 | | -24+x=x+11 | | 5(y-8)/3=-4y | | 3(x-4.3)=3.6 | | 6/10-4/10 | | 2340=45(p+25) | | 2b+24=-4b+18 | | -6.8(x-2.25)=13.6 | | 6(7x-6)+1=42x-35 |

Equations solver categories